The building of a Mediterranean identity in television: strategies and communication. The example of France 3 Corse Via Stella - Lisa D’ORAZIO (Essachess, 2011)
Now, issues of identity and representation are at the heart of media debates or historical. This concept of regional identity is, indeed, largely mobilized by the actors in these media networks. We chose to direct our communication on the question of media coverage of regional identities in France by referring to the case of Corsica.For, in Corsica, the themes of community and cultural identity are now at the heart of political debates island. The fact insular (island, image ...) precisely defines the contours of this "community" human. It enabled the flourishing of culture, language and structures of society homogeneous, despite significant regional differences in micro. Now, television is becoming a major issue to try to impose this cultural revival, especially as regards the issue of regional television. What is the role of of television in promoting this culture?